Healthy Living for Elders: High Blood Pressure - Leigh Ann Martin (EDIS)
High blood pressure is increased pressure of blood on the blood vessels. This creates more work for the heart. Another name for high blood pressure is hypertension. About 50 million Americans may have hypertension. Many are not even aware they have a problem. This document, FCS8599-Eng, is one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: March 2004.